Electroluminescence properties of a PIN structure made by nearly stoichiometric a-SiCx:H active layer - Sel, Kivanc; Akaoglu, Baris; Ozdemir, Orhan; Atilgan, Ismail (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
a-SiCx:H PIN diode has been fabricated within a single pump-down process under the same deposition conditions used for doped and undoped PECVD grown thin films, whose optical and electrical properties are determined and compared with a-Si:H. Current-voltage characteristics of PIN diode are evaluated and concluded to be limited by tunnelling of holes at p-i interface into valence band tail states. Electroluminescence measurements revealed radiative monomolecular recombinations. Deconvolution of the luminescence spectra is utilized to analyse recombination mechanism to be dominated by the transitions between band tails and deep states, which are created by the large density of both silicon and carbon dangling bonds, probable in the stoichiometric a-SiCx:H film. Finally, a small luminescence peak around 1.9 eV would be an evidence of reduced probability of tail to tail transitions, than that of the transitions between tail and deep states. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Amorphous silicon carbide; PECVD; Pin diode; Energy band gap; Conductivity; Electroluminescence; SILICON-CARBON ALLOYS; CHEMICAL-VAPOR-DEPOSITION; AMORPHOUS-SILICON; OPTICAL-PROPERTIES; THIN-FILMS; DIODE; Materials Science; Physics